Bibliometric analysis and evidence of clinical efficacy and safety of digital pills - Litvinova, Olena; Klager, Elisabeth; Yeung, Andy Wai Kan; Tzvetkov, Nikolay T.; Kimberger, Oliver; Kletecka-Pulker, Maria; Willschke, Harald; Atanasov, Atanas G. (Frontiers in Pharmacology, 2023)
Objectives: Digital pills are new technologies that aim to improve healthcare by increasing medication adherence. The aim of the work was a bibliometric analysis of clinical studies of digital pills and an assessment of the level of evidence of their effectiveness, safety, and prospects for the future. Materials and Methods: The studies were conducted using online databases such as ClinicalTrials.gov, Dimensions, and Web of Science for the period January 2012 to July 2022. The VOSviewer tool for building and visualizing bibliometric networks was used. Results: Bibliometric analysis of the scientific literature revealed that over the past 10 years, the number of publications about digital pills has noticeably increased, which indicates the increasing importance of this field of knowledge. The leading positions in this area are occupied by scientists from the United States, the United Kingdom, and India. Sources of financial support for authors of publications in the field of digital pills are funds from leading developer companies, budget allocations, and funds from non-commercial organizations. Public-private partnerships are an important path to develop and implement digital pills. The four main clusters of digital pill studies were highlighted and visualized: efficacy and safety analysis for serious mental disorders; treatment and costs of tuberculosis therapy; features of the treatment of diabetes, cardiovascular diseases, and AIDS; and usage monitoring. Available publications demonstrate the efficacy potential and safety of digital pills. Nevertheless, the effects of digital pills have not yet been fully studied. Conclusion: Priority areas for future research are further randomized controlled clinical trials and meta-analyses, which are necessary for a high level (I level) of evidence for therapeutic applications of digital pills, as well as pharmacoeconomic studies.